CHANGES IN POLITICAL CULTURE AMONG YOUNGER GENERATIONS TRIGGER LOSS IN TRUST IN DEMOCRACY AND PREFERENCE FOR TECHNOCRATIC ALTERNATIVES - Sascha Hannig Núñez (Politology, 2023)
Democratic values are on the crossroads, facing threats such as polarization, economic uncertainty, social unrest, disinformation or the challenge of raising authoritarian and illiberal regimes. When understanding changes and proposing measures to strengthen political culture, younger generations should come to the center of the debate, as this cohort will be the one to consolidate said trends for better or worse. The youngest voting generation (centennials) will be among the most affected by the long-term the effects of the pandemic; the scaling geopolitical tensions and the overall decrease in democracy across the world that high-impact studies have warned about. This piece will address one of the key characteristics that this generation exhibits when analyzing their political values: the support for technocracy and even census voting. The World Values Survey (WVS)’s last edition measures citizens decision-making preferences, which was crossed with 38 “Free” countries in the Freedom in the World report 2021. Partial results show that “expert decision making" over “politicians” is stronger in people under 29 years old in developed countries, when compared to the average population. In the case of recently-established democracies, the difference between generations was mixed. Several interpretations can be withdrawn from these results, and the recommendations towards strengthening political culture should not ignore this reality and rather address it to consolidate democracy instead of leaving room for authoritarian technocratic narratives to penetrate across the youth